Eduardo Rabossi. In memoriam - Gutiérrez, Carlos (2006)
On October 26th, 2006, in the city of Salvador de Bahia, Brasil, the Interamerican Society of Philosophy  organized an Academic Homage in memory of Eduardo Rabossi. The homage took place in the context of the XII National Philosophical Meeting in Brazil, organized by the Associação Nacional de Pós-graduação em Filosofia (ANPOF), at which time also an Extraordinary Assembly of the Society took place. The texts we include in what follows were read at that Homage.